A dynamic hybrid protection scheme for on-site emergency power system operated through an integrated microgrid during station blackout in NPP. (March 2023) - Khatua, Subhakanta; Mukherjee, V.
Highlights: Application of integrated microgrid (IMG) into the emergency power system (EPS) for a 460 MWe NPP has been considered as test station to address the station blackout problems. The protection issues in the in EPS in NPP stations are discussed in brief. Dynamic hybrid protection (DHP) scheme consisting of differential and adoptive over-current protection functions with automatic switchover-logic mechanism is proposed in this article. Different case studies are simulated by using EMTP software to qualify this novel protection scheme and results were analyzed. Harmonics analysis for this test station has been carried out by using MATLAB/Simulink software and findings were highlighted. Finally based on the simulation results, possible suggestions are given to adopt the DHP scheme for IMG operated EPS of NPP. Abstract: Post Fukushima nuclear disaster, application of renewable energy operated integrated microgrid (IMG) into nuclear power plants for strengthening the station blackout (SBO) power supply becomes popular. The IMG powered emergency-SBO (EM-SBO) is a bidirectional power system which leads to substantial variation in fault current. On the other hand, as per the guidelines of nuclear regulatory authority, minimum protection scheme is to be provided for EM-SBO power system to avoid unnecessary tripping of the safety power system. This scenario is a challenging task and a serious concern to provide suitable protection mechanism. To address this issue, a dynamic hybrid protection (DHP) scheme (hybrid differential and adaptive overcurrent protection scheme) is proposed. The proposed DHP scheme has been validated in EMTP-rv and DigSILENT Power Factory simulation software followed by harmonics analysis through Simulink. Finally, the superiority of DHP scheme for IMG has been established.